Alien Seas Oceans in Space - Carroll, Michael; Lopes, Rosaly (Springer New York : Imprint: Springer, 2013)
In the early days of planetary observation, oceans were thought to exist in all corners of the Solar System. Carbonated seas percolated beneath the clouds of Venus. Features on the Moon's surface were given names such as "the Bay of Rainbows" and the "Ocean of Storms." With the advent of modern telescopes and spacecraft exploration these ancient concepts of planetary seas have been replaced by the reality of something even more exotic. Alien Seas serves up the current research, past beliefs, and new theories to offer a rich array of the "seas" on other worlds. It is organized by location and by the material composing the oceans under discussion, with expert authors penning chapters on their  specialty. Each chapter features new original art depicting alien seas, as well as the latest ground-based and spacecraft images. With the contributors as guides, readers can explore the wild seas of Jupiter's watery satellite Europa, believed similar in composition to battery acid. Saturn's planet-sized moon Titan seems to be subject to methane or ethane rainfall that become vast lakes and, perhaps, seasonal oceans. Titan and Mars have seas of sand, large shifting dunes covering huge plains, while Venus may have 'oceans' of frozen lava. The possibilities are excitingly endless and ripe for exploration. Contributors: Kevin Baines Jeffrey Bennett James Cameron Michael Carroll Mona Delitsky David Grinspoon Rosaly Lopes Christopher P. McKay Karl Mitchell Robert Pappalardo Timothy Parker Jani Radebaugh John Spencer.